Corporate Community Involvement: How and Why 5 UK Corporations Engage in CCI - Morvan, James (2008)
The UK has witnessed a large rise in corporate community involvement (CCI) since the early 1990s, part of the wider corporate drive towards social responsiveness and corporate citizenship. An increasing amount of corporate resources are going towards CCI activity, with corporate donations reaching ÃÂ£630m in 2002/03. Five corporations have been identified as CCI leaders and/or innovators in the UK, and their communications to stakeholders will be analysed. The aim is to further understand what approaches they are undertaking, why they are participating in these activities, and how stakeholders are being engaged. This will provide insight into both how seriously these corporations take their stakeholder relations, and what degree of accountability there is towards stakeholders for their CCI initiatives; namely communities and shareholders.